Modelo de gestión del área de triaje y sus efectos en la calidad de atención de los pacientes de la emergencia del Hospital de especialidades Abel Gilbert Pontón en la cuidad de Guayaquil. - Cando Albuja, Mirna del Rocío (2015)
Hospital emergency services show weaknesses in the management of human resources, which leads to failure of the containment systems consultations, generating high production costs, poor quality and dissatisfaction among users. It means triage, or screening needs an effective system of care work order to rationalize the time and daily consultations in emergency services and hospital emergency and make intelligent use of resources. It is necessary to conduct a comprehensive management of human resources in these knowledge-based user needs as epidemiological profiles of human capital and applying the theories of needs, expectations and satisfactions (Macias-méndez.b & quijije-Chavez systems x, 2009) and administrative principles. Undoubtedly, the attention to the accident and emergency hospitals is a real and serious problem. At present caul guidelines in this research work to find an appropriate solution in improving the attention of users in emergency services